Patriotic resistance against Italian invasion in Sadan Sooddoo Oromo (1936-41) - Gemechu Kenea , Surafel Adissu (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of this paper is to highlight the resistance made by Sadan Sooddoo Oromo patriots against Italians during 1936-41. Qualitative research methodology with Purposive sampling technique was employed in this study and the relevant respondents from the target group were selected carefully by the researcher to get reliable and rich data. Available primary and secondary sources, the paper seriously took those in to account. In this paper the Sadan Sooddoo resistance, the notable partiots and the battle fought with Italians during the period was discussed and analyzed. This study casts some light on how the patriots made struggle against colonizer. This paper argued that, even though Haile Sillasie I was fled to outside after the battle of Maichew the patriots including Sadan Sooddo Oromo patriots pay great scarification and made struggle against Italian colony until the liberation of 1941.